In Vitro Activities of DU-1102, a New Trioxaquine Derivative, against Plasmodium falciparum Isolates - Basco, Leonardo K. (American Society for Microbiology, 2001)
The antimalarial trioxaquine derivative DU-1102, synthesized by covalent linkage between aminoquinoline and trioxane moieties, was highly active against Cameroonian isolates (mean 50% inhibitory concentration of 43 nmol/liter) of Plasmodium falciparum. There was no correlation between the responses to DU-1102 and chloroquine and only a low correlation between the responses to DU-1102 and pyrimethamine, suggesting an independent mode of action of the trioxaquine against the parasites.